Electrochemical Conversion of Dichloroacetic Acid to Chloroacetic Acid in Conventional Cell and in Two Microfluidic Reactors. Issue 1 (18th December 2013) - Scialdone, Onofrio; Galia, Alessandro; Sabatino, Simona; Vaiana, Giovanni Marco; Agro, Diego; Busacca, Alessandro; Amatore, Christian
Abstract The electrochemical conversion of dichloroacetic acid to chloracetic acid is investigated in conventional cells and in microreactors. Two different microreactors are used: the first is a filter press cell equipped with PTFE micrometric spacers, easy to assemble and disassemble and available for a large variety of electrodes and solvents; the second is made using an adhesive spacer, micromilling and press and could easily be developed on an industrial scale. The electrochemical synthesis is performed successfully in the microreactors equipped with a graphite cathode under proper operative conditions. The performance of the process strongly depends on the nature of the cathode and, for microreactors, on flow rate and current density. Both microreactors give high conversions and selectivity under a single‐pass mode and are allowed to work without supporting electrolyte at low cell voltages.